2019
DOI: 10.1186/s12870-019-1741-y
|View full text |Cite
|
Sign up to set email alerts
|

The mycorrhizal pathway of zinc uptake contributes to zinc accumulation in barley and wheat grain

Abstract: Background Increasing zinc (Zn) concentrations in crops is important for alleviation of human Zn deficiency. Arbuscular mycorrhizal fungi (AMF) contribute to plant Zn uptake, but their contribution to Zn in the edible portion of crops has not yet been investigated. This study aimed to quantify the mycorrhizal pathway of Zn uptake into grain of wheat and barley under varying soil Zn availabilities. Bread wheat ( Triticum aestivum ) and barley ( Hordeum vulga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
59
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 96 publications
(67 citation statements)
references
References 53 publications
7
59
0
1
Order By: Relevance
“…Conversely, in an experiment of field inoculation with the same AMF isolate, at early crop stages, Ercoli et al [21] did not find any difference in Fe and Zn concentration in shoots and roots of durum wheat. This can be explained by multiple factors, such as soil Zn deficiency found in the present study, differential response of wheat species/varieties and a large compatibilty at early stages of bread wheat with the inoculated AMF isolate [22].…”
Section: Plant Growth and Micronutrient Uptake At Gs30mentioning
confidence: 69%
See 2 more Smart Citations
“…Conversely, in an experiment of field inoculation with the same AMF isolate, at early crop stages, Ercoli et al [21] did not find any difference in Fe and Zn concentration in shoots and roots of durum wheat. This can be explained by multiple factors, such as soil Zn deficiency found in the present study, differential response of wheat species/varieties and a large compatibilty at early stages of bread wheat with the inoculated AMF isolate [22].…”
Section: Plant Growth and Micronutrient Uptake At Gs30mentioning
confidence: 69%
“…The AM symbiosis is known for improving plant access to mineral nutrients, through the development of an extraradical mycelium, consisting of a complex and extensive network of hyphae spreading into the soil [71]. The active role of AMF in the uptake and transport of minerals needed for plant growth has been demonstrated in various plant/AMF isolate combinations (e.g., P [72,73]; N [74,75]; Zn [22,76]; Fe, Cu, Mn [19]. The effectiveness of the AM symbiosis for plant nutrient uptake was studied in bread wheat (Triticum aestivum L.) [77][78][79] and durum wheat (Triticum durum Desf.)…”
Section: Plant Nutrient and Micronutrient Concentrations At Maturitymentioning
confidence: 99%
See 1 more Smart Citation
“…Managed effectively, AM fungi provide a tool for improved crop Zn nutrition in the field, particularly on Zn-deficient soils (16). Radioisotope tracing studies have demonstrated that the AM fungus Rhizophagus irregularis can contribute as much as 25% of shoot Zn uptake in tomato plants, 24% of grain Zn in wheat, and 12% in barley (17,18).…”
Section: Introductionmentioning
confidence: 99%
“…Minimum soil disturbance could also allow suitable conditions for the promotion of the abundance and diversity of symbiotic fungi, such as arbuscular mycorrhizal fungi (AMF), as well as shifts of their community structures (Alguacil et al, 2008; Brito et al, 2012). Arbuscular mycorrhizal fungi can improve soil aggregation and structure on one side, and enhance plant growth, crop production, plant nutrient status and health on the other side (Ercoli et al, 2017; Caruso, 2018; Powell and Rillig, 2018; Zhang et al, 2018; Coccina et al, 2019). However, according to a recent meta-analysis, the response of soil microbial diversity to tillage is highly variable depending on climatic conditions and soil properties (de Graaff et al, 2019).…”
Section: Introductionmentioning
confidence: 99%